EFEK KOMBINASI TAPAK LIMAN (ELEPHANTOPUS SCABER L.) DENGAN ANTIBIOTIK AMOXICILLIN, CHLORAMPHENICOL DAN COTRIMOXAZOLE TERHADAP DAYA PERTUMBUHAN BAKTERI S. AUREUS DAN E. COLI SECARA IN VITRO - Verryna Yaumi M.A (Jurnal Kedokteran Komunitas, 2018)
Introduction: Antibiotics are widely used as initial treatment for infections. But the use of antibiotics that can irrationally cause antibiotic resistance. In addiation to antibiotics, infections can be overcome by using herbs, one of which is Tread liman (Elephantopus scaber Linn.). This study aimed to examine the zone of inhibition (ZOI), minimum inhibitory level (MIC), and minimum bactericidal concentration (MBC) combination of antibiotics amoxicillin (AMX), chloramphenicol (CHL), and cotrimoxazole (COT) with Tread liman extract (TL) against the bacteria Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus).Method: The ZOI test uses the AZDAST method which is modiafied with a well. Interpretation of results with clear zone measurements using a ruler. The MIC test was carried out by microdialution with a 96-well plate and was assessed using spectrophotometry with a wavelength of 600 nm, macrodialution using a test tube and assessed by turbidiaty and sediamentation. KBM test to assess whether there is a colony formed after incubation for 24 hours.Results: The combination of TL with AMX, CHL and COT on E. coli is addiative, while in S. aureus the addiative are obtained in the combination of TL with AMX and COT, antagonist with CHL. Fractional Inhibitory Concentration Index (FICI) results from combination MIC TL with AMX are antagonist in both bacteria, other antibiotics are addiative. Fractional Inhibitory Concentration Index (FBCI) results from the combination MBC of TL with AMX, CHL and COT were addiative to E. coli, in combination with S. aureus TL with AMX and COT were addiative, while CHL was antagonist.Conclusion: In the combination ZOI test TL with CHL in S. aureus is antagonist. The combination of TL with AMX in both bacteria is antagonist. In the combination MIC test TL with CHL on S. aureus is antagonist in the KBM test. Whereas in other combinations of antibiotics are addiative.